Land Value Capture as Financial Resource for Infrastructure Development in Palembang City - Mabrurotunnisa; Doddy Aditya Iskandar (Pusbindiklatren Bappenas, 2021)
Indonesian local governments still depend on the state budget to fund infrastructure development. On the other hand, land value capture (LVC) is suitable for developing countries, such as Indonesia, to fund such development. However, there is an absent legal system to explicitly implement LVC in Indonesia. This paper aims to discuss factors affecting LVC implementation in the context of Palembang. Through an in-depth interview with several experts, the study identified existing issues affecting LVC implementation including delays in revising regulation; risk of corruption, collusion, and nepotism; decrease in public participation; and public complaints due to property tax increase. Finally, we proposed strategies that should be fulfilled by the local government for the successful implementation of LVC in Palembang. They include the establishment of an implementing agency with a clear division of role and skillful members, the enactment of specific regulations, and the establishment of a special forum, e-platform, and mass media.